2020
DOI: 10.2337/db2020-01
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Diabetic Foot Infections

Abstract: The first sections herein cover the impact of infection on healing of experimental wounds (p. 2), the importance of biofilms (p. 4), and a general overview of the microbiology of DFIs (p. 6). Although debridement of DFUs was covered in the first compendium, we deemed it important enough to include here as well, given its pivotal role in the management of DFIs. Subsequent sections cover the management of infected DFUs (p. 9) and discussions of antibiotics versus surgery for osteomyelitis (p. 12) and the OVIVA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 59 publications
1
52
0
3
Order By: Relevance
“…[ 34 ] and Boulton et al . [ 30 ] also reported Pseudomonas as the most common isolate which was similar to the present study. In the present study, Staphylococcus aureus was sensitive to amikacin and gentamicin (100%), ofloxacin (90%), vancomycin (85%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…[ 34 ] and Boulton et al . [ 30 ] also reported Pseudomonas as the most common isolate which was similar to the present study. In the present study, Staphylococcus aureus was sensitive to amikacin and gentamicin (100%), ofloxacin (90%), vancomycin (85%).…”
Section: Discussionsupporting
confidence: 91%
“…Diabetic foot infections in India are commonly caused by gram-negative bacilli. [ 30 ] There are many studies from West like Mendes et al . [ 25 ] which have reported predominance of Gram positive organisms in diabetic foot ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…A balanced redox state is likely critical for prompt healing. Diabetic skin appears to be infiltrated with more inflammatory cells, edema, and less granulation tissue formation than the normal skin, suggesting a deterioration in diabetic ulcer healing reserve [ 2 , 7 ].Additionally, the periwound and central wound tissue in people with diabetes appears to also be more likely to be prone to excessive oxidative stress and damage, which results in poor healing [ 12 , 13 ]. Kim et al suggested that both high oxidative stress levels and bacteria set the wound up for chronic wound development [ 14 ].…”
Section: Oxidative Stress State In the Development And Healing Of mentioning
confidence: 99%
“…The mechanism of diabetic wound chronicity has not been well understood. It is currently believed that oxidative stress plays a vital role in the occurrence and development of diabetic wound [ 2 , 3 ]. Oxidative stress is caused by overproduction of reactive oxygen species and insufficient antioxidant systems.…”
Section: Introductionmentioning
confidence: 99%
“…Along with monobacterial infections, polybacterial colonization of DFUs is also frequently reported 11,12 . The majority of these polybacterial infections show co‐existence of S. aureus and P. aeruginosa 13 .…”
Section: The Landscapementioning
confidence: 99%